Light dependence in the phototrophy–phagotrophy balance of constitutive and non-constitutive mixotrophic protists - Schenone, Luca (2022)
Mixotrophic protists display contrasting nutritional strategies and are key groups connecting planktonic food webs. They comprise constitutive mixotrophs (CMs) that have an innate photosynthetic ability and non-constitutive mixotrophs (NCMs) that acquire it from their prey. We modelled phototrophy and phagotrophy of two mixotrophic protists as a function of irradiance and prey abundance. We hypothesised that differences in their physiology (constitutive versus non-constitutive mixotrophy) can result in different responses to light gradients. We fitted the models with primary production and bacterivory data from laboratory and field experiments with the nanoflagellate Chrysochromulina parva (CM) and the ciliate Ophrydium naumanni (NCM) from north Andean Patagonian lakes. We found a non-monotonic response of phototrophy and phagotrophy to irradiance in both mixotrophs, which was successfully represented by our models. Maximum values for phototrophy and phagotrophy were found at intermediate irradiance coinciding with the light at the deep chlorophyll maxima in these lakes. At lower and higher irradiances, we found a decoupling between phototrophy and phagotrophy in the NCM while these functions were more coupled in the CM. Our modelling approach revealed the difference between both mixotrophic functional types on the balance between their nutritional strategies under different light scenarios. Thus, our proposed models can be applied to account how changing environmental conditions affect both primary and secondary production within the planktonic microbial food web.